Notes on Early Land Plants Today. 64. Nomenclatural notes in Balantiopsidaceae - Engel, John J.; Váňa, Jíři; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2014)
During the preparation of the forthcoming world checklist of hornworts and liverworts (Söderström et al., in press.) it was noted that a few taxa need to be validated or combined. The subfamily name Balantiopsidoideae has been used as if it has been an autonym of the family Balantiopsidaceae H.Buch (1955: 23) (e.g. Grolle 1972, Engel & Smith Merrill 1997). However, as autonyms do not exist on any other taxonomic level than genus or species (ICN 22.3, 26.3; McNeill et al. 2012) all subfamilies need to be accompanied by a valid description or diagnoses or a reference to an effectively published description or diagnoses (ICN Art. 39.1).